2010
DOI: 10.1258/ebm.2010.009353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electro-acupuncture on endothelium-derived endothelin-1 and endothelial nitric oxide synthase of rats with hypoxia-induced pulmonary hypertension

Abstract: Pulmonary hypertension (PH) is characterized by elevated pulmonary artery pressure (PAP), pulmonary vascular remodeling and right ventricular hypertrophy, which are mainly due to endothelial dysfunction. Electro-acupuncture has shown beneficial effects on cardiovascular homeostasis, but little evidence has been obtained on pulmonary effects. The goal of the present study was to investigate whether electro-acupuncture on bladder-13 and -15 points can protect against chronic hypoxia-induced PH by regulating endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…A pilot, randomized, double-blind, placebo-controlled crossover trial (Park et al, 2010) showed that flow-mediated dilation was significantly improved with the acupuncture treatment at ST36 and ST36 plus PC6, whereas floor-mediated dilation was unchanged after the acupuncture treatment at PC6 or the sham treatment. Indeed, basic experiments, investigating the mechanisms of acupuncture on regulating endothelial function in rats with hypoxiainduced pulmonary hypertension or with stress-induced hypertention, confirmed that verum acupuncture significantly improved circulation eNOS concentration and markedly increased calcitonin gene-related peptide and nitrogen monoxidum in blood plasma, paralleling to its blood pressure reduction (Pan et al, 2010;Wang, Jing, et al, 2011;Wang, Zhang, et al, 2011).…”
Section: Cardiovascular Systemmentioning
confidence: 96%
“…A pilot, randomized, double-blind, placebo-controlled crossover trial (Park et al, 2010) showed that flow-mediated dilation was significantly improved with the acupuncture treatment at ST36 and ST36 plus PC6, whereas floor-mediated dilation was unchanged after the acupuncture treatment at PC6 or the sham treatment. Indeed, basic experiments, investigating the mechanisms of acupuncture on regulating endothelial function in rats with hypoxiainduced pulmonary hypertension or with stress-induced hypertention, confirmed that verum acupuncture significantly improved circulation eNOS concentration and markedly increased calcitonin gene-related peptide and nitrogen monoxidum in blood plasma, paralleling to its blood pressure reduction (Pan et al, 2010;Wang, Jing, et al, 2011;Wang, Zhang, et al, 2011).…”
Section: Cardiovascular Systemmentioning
confidence: 96%
“…It was proven that electroacupuncture pretreatment significantly inhibited systemic inflammatory responses and improved survival rate in rats with lethal endotoxemia [6]. Feishu (BL13) acupoint is considered of choice to treat lung diseases and regulate pulmonary functions, Pan et al reported that treatment with electroacupuncture on BL13 showed beneficial effects on hypoxia-induced pulmonary hypertention in rats [7]. Traditionally, acupuncture at Zusanli (ST36) acupoints was known as the modulation of immune functions and is often used in clinical disorders of the immune system [8].…”
Section: Introductionmentioning
confidence: 99%
“…The current 20-d IHC program of brief, normobaric, moderately intense (FIO 2 9.5-10%) hypoxia bouts did not produce right ventricular hypertrophy in Wistar rats. In contrast, normobaric or hypobaric hypoxia programs in which hypoxia exposures of a similar intensity are continuous [68][69][70] or protracted (e.g. 4-8 h bouts) 71,72 provoke right ventricular hypertrophy and medial thickening of the pulmonary vasculature in this strain.…”
Section: Discussionmentioning
confidence: 85%